Project Method: Learning by Doing - Гімаєва, Юлія Азгатівна (Проблеми сучасної освіти, 2018)
This paper considers the necessity of introducing innovative motivating methods in teaching foreign languages for increasing the activity and interest of students. The main goal is to make learning not only effective but also interesting, to involve students more actively and intensively in the learning process, to make them its main and active participants. The effectiveness of each method is conditioned first of all by explosion of motivation, by increased interest in the subject: this is the most important component of the learning process. This article reveals the importance of practicing the method of projects in teaching grammar and vocabulary of a foreign language.